1986
DOI: 10.1002/ajh.2830230306
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibrinolytic activity in patients undergoing cardiopulmonary bypass operation

Abstract: The influence of cardiopulmonary bypass on fibrinolytic activity was assessed by a sensitive clot lysis assay in eight patients undergoing coronary artery bypass operations. Fibrinolytic activity increased immediately after cardiopulmonary bypass was begun and remained elevated throughout the period of extracorporeal circulation. At the conclusion of the operative procedure, fibrinolytic activity returned to the normal range in all patients, and no subject had postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Some authors, however, found no changes in plasminogen [14], and even decreased EFA has been reported [19]. As far as plasmin inhibitors are concerned, there is evidence for a significant drop of a2-AP and other plasmin inhibitors during surgery [5,20], although some authors found no significant changes [17], Finally, the higher D-dimer levels found in our patients may have clini cal implications, as they could indicate that fibrin is newly formed in the circulation dur ing bypass as a result of decreased vascular perfusion, or in pooled blood in the heart during cardioplegia [4]. The amounts of plasmin generated as a consequence of the plasminogen activation may result in a lim ited degradation of fibrinogen, but a signifi cant degradation of cross-linked fibrin.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some authors, however, found no changes in plasminogen [14], and even decreased EFA has been reported [19]. As far as plasmin inhibitors are concerned, there is evidence for a significant drop of a2-AP and other plasmin inhibitors during surgery [5,20], although some authors found no significant changes [17], Finally, the higher D-dimer levels found in our patients may have clini cal implications, as they could indicate that fibrin is newly formed in the circulation dur ing bypass as a result of decreased vascular perfusion, or in pooled blood in the heart during cardioplegia [4]. The amounts of plasmin generated as a consequence of the plasminogen activation may result in a lim ited degradation of fibrinogen, but a signifi cant degradation of cross-linked fibrin.…”
Section: Discussionmentioning
confidence: 84%
“…The abnormalities most frequently found in clude heparin and protamine excess, heparin rebound, low platelet count, abnormal plate let function, increased fibrinolysis, and dis seminated intravascular coagulation (DIC) [6,7]. Increased fibrinolysis could contribute to postoperative bleeding, whereas a postopera tive fibrinolytic shutdown could be a risk factor taken into consideration in the ap pearance of thrombosis [4,5,8],…”
Section: Introductionmentioning
confidence: 99%
“…Increased fibrinolysis during this period has been demonstrated by several other investigators. 16,23,[31][32][33][34][35] The usefulness of EACA to treat excessive bleeding after aortocoronary bypass was reported by Lambert in 1979. 36 Using the prothrombin time, partial thromboplastin time, fibrinogen level, and tri-F titer tests, hyperfibrinolytic bleeding was the most frequently identifiable coagulation disorder and was diagnosed in 20% of the patients.…”
Section: Eaca and Ta In Cardiac Surgerymentioning
confidence: 99%
“…Ainda durante a circulação extracorpórea, devido à hemodiluição, à hipotermia, ao trauma dos elementos figurados do sangue e à liberação de substâncias vasoativas, observa-se alterações nas plaquetas, nas proteínas relacionadas à coagulação e no sistema fibrinolítico, conforme descreveram HORROW (1) , ELLISON & JOBES (2) e KUCUK et al (3) .…”
Section: Introductionunclassified